MASA DEPAN ENERGI TERBARUKAN DI LAUT: PERAN TEKNOLOGI TENAGA LAUT DALAM MITIGASI PERUBAHAN IKLIM - Yatzin Azharil, Muh; Abduh, Aimar Rendra Patanrei; Sulfa, A. Muhammad Fauzan; Husain, Firman (Riset Sains dan Teknologi Kelautan, 2025)
Human life cannot be separated from the use of energy. Energy is needed for many things like cooking, traveling, and working. Currently, electrical energy is the main need. To produce electrical energy, power plants that utilize renewable and non-renewable energy sources are needed. Technology in the field of renewable energy continues to experience rapid development. The use of renewable energy aims to reduce the impact of global climate change and reduce dependence on fossil fuels. A variety of natural resources are available as renewable energy alternatives, one of which is marine power technology. Marine energy technology is a technology that utilizes various properties and movements of the ocean to generate electrical energy. Energy sources from the sea can be utilized by using marine technology such as ocean current technology, ocean wave technology, and ocean thermal energy conversion. This technology makes it easy to adapt to the characteristics of the exploited sea.